Catalytic hydroprocessing of fatty acids to renewable diesel using lanthanum-modified zeolite-based catalysts - Idris, Nur Azreena (2022)
The hydroprocessing of fatty acids into hydrocarbons is a viable alternative approach for producing renewable fuel with improved properties than biodiesel, which has inherent drawbacks due to its high oxygen content. Therefore, this study explored the catalytic hydroprocessing of fatty acids into renewable diesel using zeolite based-catalysts (zeolite beta and HZSM5). The optimal conditions established for both catalysts were 350 °C, 4 MPa hydrogen pressure, and 5 wt.% of catalyst loading for 2 h. Zeolite beta outperformed the HZSM5 in terms of HDO reaction activity, with a diesel selectivity of 77% compared to HZSM5 (70%). Furthermore, the La(10)zeo(90) catalyst demonstrated conversion of OA up to 99% with 83% of C15 and C17 selectivity. The superior activity of La(10)zeo(90) was attributed to the synergistic interaction of La-Si-Al, a sufficient number of weak and medium acid sites, and excellent textural properties of the catalyst. Interestingly, when La(10)zeo(90) was applied to palm fatty acid distillate (PFAD) for the renewable diesel production, catalytic deoxygenation (DO) and HDO reactions were involved. The DO reaction was carried out at 350 °C in a nitrogen environment with 5 wt.% catalyst loading for 3 h reaction time, whereas the HDO reaction was carried at 400 °C and 5 MPa, respectively. Remarkably, the HDO reaction of PFAD produced renewable diesel (RD 100) containing 73% of C16 selectivity, whereas the DO reaction produced 51% of C15 via the deCOx route. The RD 100 produced via the HDO and DO reactions met ultra-low sulphur diesel (ULSD) specifications, indicating that it can be used directly in automobile engines or blended with conventional diesel to significantly improve the fuel characteristics profile. Meanwhile, the performance of La(10)HZSM5(90) was evaluated using used frying oil (UFO) and PFAD, using 5 wt.% catalyst loading, 2 h reaction time, 5 MPa H2 pressure, and 400 °C. The diesel yields were 85% (UFO) and 93% (PFAD) respectively. The UFO showed a selectivity of 19% for C17 fraction and 51% for C20 fraction while PFAD exhibited C15 (48%) and C20 (29%). Additionally, the La(10)HZSM5(90) catalyst exhibited a promising cycle with five consecutive runs despite coke formation.